The Relation Of Mother's Age And Exclusive Breasting Attainment In Pajangan Primary Health Centre - rahayu, septi (Sahabat Publikasi Kuu, 2023)
Background: Exclusive breastfeeding in Indonesia has not been fully implemented. One of the factors which influences the failure to achieve breastfeeding is the mother's age. Based on the data from Central Bureau of Statistics, Yogyakarta only recorded a decline in the achievement of exclusive breastfeeding; in 2019 the number fell to 74.90%, in 2020 the number became 78.93, and in 2021 the number fell to 77.00%. Purpose: The study is to determine the relation of mothers’ age and the attainment of exclusive breastfeeding at Pajangan Primary Health Center. Method: The study employed quantitative method with case control design. There were 200 populations, 62 samples, and 31 groups of cases which were taken by total sampling. In addition, 31 control samples were taken by purposive sampling. Retrieval of data using secondary data. Univariate analysis was in the form of frequency distribution and bivariate analysis used the Chi Square test. Results: The study was conducted by analyzing the relation of mothers’ age and the attainment of exclusive breastfeeding and obtained p value <0.05 (p-value = 0.012) and an OR of 3.645. Therefore, it can be concluded that there is a relation mothers’ age and the attainment of exclusive breastfeeding. Conclusion: There is a relation of mothers’ age and the attainment of exclusive breastfeeding.